CHEMICAL, PHYSICAL AND SENSORY CHARACTERISTICS OF SIAM CATFISH MEATBALL (Pangasius hypophthalmus) SUBSTITUTED BY BETUNG BAMBOO SHOOTS (Dendrocalamus asper) - Astuti, Sussi (Jurusan Teknologi Hasil Pertanian, 2025)
Betung bamboo shoots are a high-fiber food ingredient that can be used to make siam catfish meatballs. This study aims to determine the effect of substituted betung bamboo shoots at various concentrations on the chemical, physical, and sensory properties of siam catfish meatballs and to find the optimal concentration of betung bamboo shoots that produces the best properties. The study used a Complete Randomized Block Design (RAKL) with 6 treatments of siam catfish meat and betung bamboo shoots ratio: F1 (100%:0%), F2 (90%:10%), F3 (80%:20%), F4 (70%:30%), F5 (60%:40%), and F6 (50%:50%). Data were analyzed for variance homogeneity using Bartlett's test and additivity using Tukey's test. Analysis of variance (ANOVA) was conducted to determine the treatment effects, followed by the Least Significant Difference (BNT) test at a 5% level. The results showed that the formulation of siam catfish meatballs substituted with betung bamboo shoots had a significant effect on moisture content, ash content, hardness, springiness, cohesiveness, texture, aroma, taste, and overall acceptance. F2 was the best treatment with moisture content of 73.58%, ash content of 1.62%, hardness of 56.13 N, springiness of 2.58 mm, cohesiveness of 0.87 mm, texture score of 4.41 (compact), taste score of 4.30 (like), aroma score of 3.93 (like) overall acceptance score of 4.25 (like), protein content of 7.91%, and fiber content of 1.44%.